METODE KLASIK VS KONTEMPORER METODE STUDI ISLAM - Bayu Bambang Nurfauji; Intan Putri April Liyanti; Febrianti Aqmal Risanti; Dina Istiqomah; Desi Ratna Ningsih (Adisam Publisher, 2026)
Islamic education is an important pillar in forming personality and Islamic civilization from the time of the Prophet to the current contemporary era. This study aims to examine the development of Islamic educational thought from the classical era, medieval, modern and contemporary through a literature study approach. Era The classics are characterized by the thoughts of scholars such as Al-Ghazali and Ibn Sina emphasizes harmonization between religious knowledge and rationality. In the medieval era, educational thinking is more focused on the institutionalization of education with the emergence of madrasas and formal curricula. Meanwhile, in the modern era, this happens transformation of thought due to the influence of colonialism and the rise of the Islamic world, with figures such as Muhammad Abduh and Syed Naquib al-Attas. In the contemporary era, Islamic education faces the challenges of globalization, digitalization, and issues of relevance and integration of Islamic values in the context of modern society. Study results shows that Islamic educational thought continues to undergo evolution with maintaining basic Islamic values while adapting to the challenges of the times. The implication of this study is the need for curriculum and strategy formulation contextual and transformative learning so that Islamic education remains relevant and solutions to the problems of the times. This study also encourages development critical and innovative thinking in Islamic education based on the values of monotheism, humanity, and justice.